A nanoscale p–n junction photoelectrode consisting of an NiOx layer on a TiO2/CdS nanorod core-shell structure for highly efficient solar water splitting - Yoo, Il han; Kalanur, Shankara S.; Seo, Hyungtak (Applied Catalysis B: Environmental, 2019)
The TiO2/CdS system has attracted great attention in solar water-splitting applications owing to its desirable electronic and optical properties. With the aim of enhancing its photoelectrochemical water splitting efficiency, an efficient strategy is proposed via nanostructuring and linking it in a p–n junction configuration with NiOx. The deposition of TiO2 nanorods (NRs) and CdS was achieved using a hydrothermal synthesis route in the sequence, after which NiOx was deposited via RF magnetron sputtering. Characterisation revealed the uniform deposition of CdS onto the TiO2 NRs, forming a core-shell morphology, and the deposition of NiOx on top of the TiO2-NR/CdS resulted in a nanostructured p–n junction. X-ray photoelectron spectroscopy was used to resolve the valence band edge, and impedance studies confirmed the formation of a p–n junction; accordingly, the probable band edge positions of the photoelectrode were identified. The optimised TiO2-NR/CdS-NiOx p–n junction electrode exhibited a remarkable photocurrent of ˜30 mA cm−2 (at 1 V vs. Ag/AgCl) under AM 1.5 G simulated sunlight and an incident photon-to-current efficiency of ˜97% at 500 nm. Furthermore, during illumination, the production of H2 gas occurred with a faradaic efficiency of 95%. The results of the study demonstrate the advantage of utilizing the TiO2-NR/CdS-NiOx system in a p-n junction configuration to greatly enhancethe charge generation, separation and suppression of the charge recombination, which boosts its photoelectrochemical water-splitting performance.
Keywords: Band alignments; Core-shell morphologies; Electronic and optical properties; Incident photon-to-current efficiencies; NiOx; Photoelectrochemical water splitting; Photoelectrochemical water splitting efficiencies; TiO2; Band alignment; CdS; NiOx; Photoelectrochemical water splitting; p–n Junction; TiO2